Analisis Kesenjangan Implementasi Aplikasi SRIKANDI dalam Meningkatkan Efektivitas Pengelolaan Arsip di Kementerian Agama Kabupaten Sidoarjo - Muhammad Rizki Dwi Kurniawan; Risalatul Lailiya; Riza Nur Khikmiah; Sahudi Sahudi; Lilik Huriyah (Jurnal Serasi, 2026)
This study investigates the strengths and weaknesses of the SRIKANDI application implementation to improve the effectiveness of archive management at the Ministry of Religious Affairs in Sidoarjo Regency. The digitization of archives is a strategic step that supports efficient and modern document management in government agencies. The SRIKANDI, a technological innovation, accelerates the transformation of archive management, including data recording, tracking, and security. This study uses a descriptive qualitative method with data collection techniques including observation, in-depth interviews, and documentation. SRIKANDI application, a technological innovation, accelerates the transformation of archive management, including data recording, tracking, and security. This study uses a descriptive qualitative method with data collection techniques including observation, in-depth interviews, and documentation. The optimization system was hampered by implementation errors, particularly human errors, infrastructure issues, such as unstable internet connections, and system errors caused by server issues. Utilizing in-depth interviews and direct observation of the institution's archiving process, this qualitative study employed primary data collection methods